EDUKASI EDUKASI MEDIA PEMBELAJARAN EDMODO SEBAGAI SOLUSI PEMBELAJARAN DARING DI SDN 180 N PEKANBARU DENGAN MEMANFAATKAN STRATEGIC ALIGNMENT MODEL (SAM) - Maulana Rezfajri S; Yutiandry Riavai; Surya Safari; Peri Akri; Bob Novitriansyah (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
The Covid-19 pandemic has had a considirable impact on education in Indonesia. The implementation of learning that was originally offline changed to online and caused various problems in its implementation. As happened in SD Negeri 180 Pekanbaru, where teachers are less adept at utilizing the various learning platforms available so only use the WhatsApp application only. In this devotion, the practitioner uses Edmodo for student learning assistance to be more attractive and effective, because in the application of edmodo features are provided more fully such as the creation of problem banks, video conferences, classrooms, and many other features that can support teaching and learning activities. The devotional team also teaches teachers to operate Edmodo for teaching and learning activities so as not to just fixate with the WhatsApp application. The purpose of this research is to know the effectiveness of the use of Edmodo in distance learning or online in SD Negeri 180 Pekanbaru. This devotion uses the method of analysis of precisely kulalitative data case studies by utilizing strategic alignment model (SAM) literature. The results of this devotion show that students feel happy about the implementation of online learning using Edmodo. Keyword: Covid-19, Edmodo, SAM Literatur